Synthesis of 2H-azirine-2,2-dicarboxylic acids and their derivatives - Agafonova, Anastasiya V.; Novikov, Mikhail S.; Khlebnikov, Alexander F. (Beilstein Journal of Organic Chemistry, 2024)
Methods for the preparation of 3-aryl-2H-azirine-2,2-dicarboxylic acids and their amides, esters, and azides by FeCl2-catalyzed isomerization of 3-aryl-5-chloroisoxazole-4-carbonyl chlorides into 3-aryl-2H-azirine-2,2-dicarbonyl dichlorides followed by their reaction with nucleophiles are reported. Two approaches to the preparation of 3-aryl-5-chloroisoxazole-4-carbonyl chlorides have been developed.
Keywords: azirine-2,2-dicarboxamides; azirine-2,2-dicarboxylic acids; isomerization; isoxazoles